McMaster’s Evolving Digital Research Support Landscape (Version 2.0; Summer 2024) - Brodeur, Jay; Burns, Matthew; Di Nello, Angela; McNeill, Kestrel; Sharma, Ratika; Sonier, Katie; Sonnadara, Ranil; Dallaire, Tracy (My University, 2024)
This report presents findings from the Digital Research Commons Pilot’s (DRCP) Context evaluation of digital research support (i.e., access to systems, services, software, and the necessary expertise to use them effectively) at McMaster, which comprised three activities: synthesizing past assessments, identifying stakeholders and service providers, and analyzing digital research needs, gaps, and opportunities. The findings highlight the complexity of the support environment where various service providers cater to diverse researcher needs, but also reveal a lack of coordination, resulting in challenges associated with service discovery, access, and alignment with researchers' expectations.
Keywords: digital research support; digital research infrastructure